2012
DOI: 10.1038/bmt.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis is linked to severe acute GVHD in patients with Fanconi anemia

Abstract: Fanconi anemia (FA) patients have an increased risk of acute GVHD (aGVHD) after hematopoietic SCT, with hypersensitivity to DNAcross-linking agents and defective DNA repair. MicroRNA-34 and p53 can induce apoptosis after DNA damage.Here we assessed epithelial cell apoptosis, and studied TP53 and miR-34a expression in the skin and gut biopsies in five non-transplanted FA patients, in 20 FA patients with aGVHD and in 25 acquired aplastic anemia patients (AA). Epithelial apoptosis was higher in FA than in acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
(24 reference statements)
1
31
0
3
Order By: Relevance
“…Previous studies indicate that microRNAs (miRs) play critical roles in the pathogenesis of aGVHD, including but not limited to miR-155, miR-146a, miR-181a, miR34a, and miR-100 (refs. 7-10). These miRs were found differentially expressed in effectors cells associated with aGVHD such as T cells subsets and antigen presenting cells (APCs) and modulate aGVHD by affecting mostly T cell function (7-10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that microRNAs (miRs) play critical roles in the pathogenesis of aGVHD, including but not limited to miR-155, miR-146a, miR-181a, miR34a, and miR-100 (refs. 7-10). These miRs were found differentially expressed in effectors cells associated with aGVHD such as T cells subsets and antigen presenting cells (APCs) and modulate aGVHD by affecting mostly T cell function (7-10).…”
Section: Introductionmentioning
confidence: 99%
“…7-10). These miRs were found differentially expressed in effectors cells associated with aGVHD such as T cells subsets and antigen presenting cells (APCs) and modulate aGVHD by affecting mostly T cell function (7-10). Emerging data indicate that miRs can also be found in different body fluids such as serum, plasma, saliva and urine (11-14).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Fanconi anemia (FA), an inherited disorder characterized by developmental defects, genomic instability and progressive bone marrow failure (110), miR-34a expression in patient gut biopsies after HSCT was significantly higher in aGvHD grades II–IV compared to grade 0–I or with non-transplanted FA patient gut biopsies (111). …”
Section: Mirna and Mrna Expression Profiling In Hsctmentioning
confidence: 99%
“…A clinical trial to further establish the significance of miR-155 in aGVHD is currently ongoing (ClinicalTrials.gov Identifier: NCT01521039). In addition, a group of miRs (miR-423, miR-199-3p, miR-93*, and miR-377) [6], miR-100 [7], miR-34a [8], and miR-146a [9] has also been identified to play an important role in the process of aGVHD after allo-HSCT. Atarod et al identified eight miRs (miR-146a, miR-155, miR-515, miR-346, miR-143, miR-373, miR-310, and miR-29) which could target different molecules in the GVHD signaling pathway [10].…”
Section: Introductionmentioning
confidence: 97%